USING ALTERNATIVE TEACHING TECHNIQUES IN ENGLISH LANGUAGE TEACHING - Adrian Rodgers (Universitas Negeri Padang, 2016)
Process-oriented drama techniques are easily taught in school classrooms and in teacher preparation programs. Although they use fiction, process-oriented approaches are different than theatrical approaches in that in process approaches the participants are a witness to their own acts. There is not external audience for whom action is performed. Therefore process approaches can be used in classrooms as a way of teaching, rather than using class time for rehearsal and subsequent performance (Rodgers, 2001).Process approaches offer a welcome alternative to traditional teaching approaches, allow for students to engage in different ways, and use reading, writing, speaking, listening, observing and responding as multi-modal supports in the meaning-making process (Rodgers, 2011). In this session the author demonstrates one teaching technique – tableaux making - and works with audience members to analyze it from the perspective of the learner, teacher and teacher educator. Discussion of how the technique might be employed in school settings will be discussed.